Spatial Variability and Co-acclimation of Phytoplankton and Bacterioplankton Communities in the Pearl River Estuary, China - Zhu, Jianming; Hong, Yiguo; Zada, Sahib; Hu, Zhong; Wang, Hui (Frontiers in Microbiology, 2018)
Phytoplankton and bacterioplankton play significant roles in estuarine systems. It is important to demonstrate the spatial variability of bacterial and microalgal communities and understand the co-acclimation of these organisms to different environmental factors. In this study, MiSeq sequencing and morphological identification were applied to analyze the variations in bacterial and microalgal communities in the Pearl River Estuary, respectively. Molecular ecological network analysis was used to investigate the potential interactions between microalgae and bacteria and illustrate the responses of these interactions to environmental gradients. The results revealed that microalgal/bacterial communities in freshwater samples were distinct from those in mesohaline water samples. Microalgae affiliated to the genus Skeletonema dominated the mesohaline water phytoplankton communities, while Melosira was the more abundant genus in freshwater communities. Actinobacteria, Alphaproteobacteria, Betaproteobacteria and Acidimicrobiia dominated bacterial communities in freshwater samples, while Gammaproteobacteria, Bacilli and Synechococcophycideae were more abundant in mesohaline water samples. Tightly correlations were observed between phytoplankton and bacterioplankton. These interactions were regarded to be key factors in shaping the community structures. Further, the KEGG database and PICRUSt were used to predict the functions of bacterioplankton in the process of nitrogen cycling. The results indicated that denitrification could play an important role in nitrogen loss and might alleviate the eutrophication in the Pearl River Estuary. Collectively, the results in this study revealed that substantial changes in phytoplankton and bacterioplankton communities were correlated with the gradients of environmental parameters in the Pearl River Estuary. The results also demonstrated that the interactions between phytoplankton and bacterioplankton were important for these organisms to acclimate to changing environments.